Prostate biopsy in a rural hospital: Our experience - Suresh K Jariwala (Wolters Kluwer Medknow Publications, 2017)
Aims: We have seen middle-aged and elderly patients with lower urinary tract symptoms (LUTS) or retention of urine in our hospital. Digital rectal examination (DRE) and prostate-specific antigen (PSA) were done for workup. Prostate biopsy (PB) was done whenever indicated. We wanted analysis of PB in our rural setup. Materials and Methods: The study period includes from January 2008 to May 2012 and January 2015 to May 2016. Any patient aged 45 years or more presenting with LUTS or retention of urine was included in the study. PSA and DRE were done in all patients. Inclusion criteria were abnormal DRE or PSA ≥4 ng/ml. Exclusion criteria were immunocompromised status, coagulopathy, urinary tract infection, acute prostatitis or abscess, uncontrolled diabetes mellitus, or previous biopsy. Histopathology report was noted. Statistical Analysis: No special software was used. Author used his arithmetical skill learned in school days to do analysis. Results: One hundred and thirty-four patients were included in the study. Average age was 69 years. PSA ranged from 1 to 1700, average being 65.3 ng/ml. Prostate cancers (PCs) was found in 65 cases. Adenocarcinoma of prostate was found in 54 cases, average PSA being 110.8 ng/ml. Small cell PC (SCPC) found in 11 cases, average PSA being 55 ng/ml. Prostatic intraepithelial neoplasia was found in six cases, average PSA being 18.8 ng/ml. Conclusion: PC is not uncommon in India. Patients present in advanced stages and with high PSA values. Transrectal ultrasound-guided 12-core systematic PB is the standard to confirm diagnosis of PC. Incidence of SCPC is high in our series. They presented with high PSA values. This need further study.